Exploring Monetary Policy Effectiveness in Indonesia's Inflation: Conventional and Islamic Perspective - Wulandari, Neni Sri; Kurniaputri, Mega Rachma; Muhammad, Mumuh (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2023)
This study aims to compare the effectiveness of Islamic and conventional monetary policies in addressing inflation in Indonesia. This research is driven by the lack of comprehensive examination of the effectiveness and nuances of the dual monetary system. Additionally, the dynamics of dual monetary policies become the research gap that needs to be addressed for a more nuanced understanding of Indonesia's monetary landscape. Using the Vector Autoregression/Vector Error Correction Model and analyzing time series data from January 2013 to December 2021, the research reveals that neither sharia nor conventional instruments have immediate effects on inflation. However, specific sharia financial instruments substantially impact inflation dynamics in the long term. The study delves into the intricate relationship between these monetary instruments and inflation, shedding light on their nuanced contributions to the economic landscape. This comprehensive analysis contributes valuable insights for policymakers, economists, and stakeholders seeking a nuanced understanding of the dynamics between monetary policy and inflation in Indonesia.